UNILATERAL PROFOUND DEAFNESS - A POSSIBLE MECHANISM - Konstantin Georgiev; Yana Pacholova (Peytchinski Publishing, 2021)
Purpose: To explain the clinical findings of patients with profound unilateral deafness who have recovered the hearing function after a combined treatment of hyperbaric oxygenation and dehydrant therapy. Material and method: 11 patients with profound sudden unilateral hearing loss above 90 dB SPL, intolerance to sounds similar to recruitment, at levels 10-20 dB above the hearing threshold (105-120 dB SPL), positive glycerol test and unexpected good recovery of hearing within 1-2 months are described. Results: All patients have perfect outcome results without the use of glucocorticoids. Conclusions: Based on articles about experiments with genetically modified animals and acquired deafness, we propose a possible mechanism of damage explaining the clinical findings and the favorable outcome of the disease - a disconnection between the tectorial membrane and stereocilia. Thus mechano-electrical transducer (MET) of hair cells cannot be activated. The combined use of hyperbaric oxygenation and dehydrant medications can lead to recovery of the hearing function.